1984
DOI: 10.1128/aem.48.2.416-419.1984
|View full text |Cite
|
Sign up to set email alerts
|

Survey of sensitivity of twelve yeast genera toward T-2 toxin

Abstract: A survey was made to detect the sensitivity of 12 yeast genera to T-2 toxin. Seventy-five yeasts isolated from various sources were tested for their susceptibility to T-2 toxin. The MIC of T-2 for these yeasts varied from 1.0 to greater than 8.0 jig/ml. Of the yeasts studied, Kluyveromyces fragilis showed the greatest sensitivity, which ranged between 0.5 and 2.5 ,ug of T-2 toxin per ml of culture medium. The roles of incubation temperature, size of the inoculum, and incubation time on the MICs were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…When two yeasts related to beer spoilage (P. membranaefaciens and H. anomala), the fission yeast used for ethanol production (S. pombe), a haploid strain of S. cerevisiae and a yeast shown by Sukroongreung et al (1984) to be sensitive to a low concentration of T-2 toxin (K. marxianus) were tested, DON, ZEA and FB 1 individually and in combination did not affect the relative growth of any of the yeasts tested (Table 1). As was expected, the relative growth of K. marxianus NCYC 100 in the presence of 2 p.p.m.…”
Section: The Effect Of a Combination Of Fusarium Mycotoxins At Low Comentioning
confidence: 99%
See 1 more Smart Citation
“…When two yeasts related to beer spoilage (P. membranaefaciens and H. anomala), the fission yeast used for ethanol production (S. pombe), a haploid strain of S. cerevisiae and a yeast shown by Sukroongreung et al (1984) to be sensitive to a low concentration of T-2 toxin (K. marxianus) were tested, DON, ZEA and FB 1 individually and in combination did not affect the relative growth of any of the yeasts tested (Table 1). As was expected, the relative growth of K. marxianus NCYC 100 in the presence of 2 p.p.m.…”
Section: The Effect Of a Combination Of Fusarium Mycotoxins At Low Comentioning
confidence: 99%
“…Hernández & Cannon (1982) demonstrated that trichothecenes (trichodermol, DAS and verrucarin A) cause inhibition of protein synthesis in Saccharomyces cerevisiae. Sukroongreung et al (1984) investigated the sensitivity of 12 yeast genera toward T-2. Of the yeasts studied, Kluyveromyces fragilis (K. marxianus) showed the greatest sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…R. pseudosolanacearum strain PD7123 (IPO4001) isolated from a rose plant in the greenhouse (Tjou‐Tam‐Sin et al ., 2017) and R. solanacearum strain IPO1828 (PD2763) isolated from potato were used in this study. The isolates were grown on yeast extract peptone glucose agar (YPGA) medium (Sukroongreung et al ., 1984), incubated at 25°C for 72 h and checked for purity. Bacterial suspensions were prepared in sterile phosphate buffer (PB) 0.01 M (2.7 g of Na 2 HPO 4 .12H 2 O and 0.4 g of NaH 2 PO 4 .2H 2 O in pH = 7.2) with an optical density (OD) at 600 nm of 0.1 (approximately 10 8 cfu mL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In these studies only one alga and one yeast were used, and there was no reason to think that either had optimal sensitivity. There can be an advantage with one yeast organism over another, as shown in the work of Sukroongreung et al [21]. They evaluated 75 yeast isolates for their sensitivity to T-2 toxin (one of the trichothecenes referred to as Yellow Rain), and found differences of an order of magnitude in their response.…”
Section: Discussionmentioning
confidence: 99%